Biomechanical properties of the Marfan's aortic root and ascending aorta before and after personalised external aortic root support surgery. Issue 8 (August 2015) - Singh, S.D.; Xu, X.Y.; Pepper, J.R.; Treasure, T.; Mohiaddin, R.H.
Highlights Patient-specific models were built to examine changes in biomechanical stresses in the aorta of Marfan patients after PEARS. Peak aortic stresses and displacements before PEARS were located at the sinuses of Valsalva but following PEARS surgery, these peak values were shifted to the aortic arch, particularly at the interface between the supported and unsupported aorta.